Sistema deflector de orientación automática para una turbina eólica tipo Savonius (2013)
Savonius wind rotors for energy production have efficiency that depends on various design parameters. One of them is the use of deflectors or elements that hinder the direct action of wind on the rotor blades that move against wind direction, or returning blades. In this sense, the design of an automatic wind deflector system is presented in this work to improve the performance and increase the efficiency of the rotor. The increase in efficiency was 9.6% when using the electronic deflector system.